THE INFLUENCE OF PLASTICIZER TYPE ON THE CHARACTERISTICS OF BIOPLASTICS MADE FROM TARO TUBER STARCH (Colocasia esculenta (L.) Schott) WITH THE ADDITION OF CANE DRAGUE CELLULOSE - Sari, Syifa Aulia Permata; Asriza, Ristika Oktavia; Adisyahputra (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2023)
The problem of plastic waste is currently still the main trigger of environmental pollution, its nature that is not easily degraded will produce more waste. One alternative to overcome this problem is to reduce the use of conventional plastics and develop plastics that are more environmentally friendly or also known as bioplastics. In this study, bioplastics made from taro tuber starch with the addition of bagasse cellulose filler were varied based on the type of plasticizer in the form of glycerol, sorbitol, and propylene glycol. The resulting bioplastics were characterized by FTIR analysis, tensile strength test, TGA test, and water absorption test. The process began with cellulose isolation from sugarcane bagasse which obtained a yield of 24.27%, then taro tuber starch extraction with a yield of 27.87%. The results of the FTIR spectrum of bioplastics did not show significant differences in the absorption of wave numbers for each variation of plasticizer types. The functional groups seen from the FTIR results are O-H, C-H, and C-O groups. Bioplastics with the addition of propylene glycol plasticizer have a high tensile strength value of 23.26 Mpa, good thermal resistance with a mass reduction of 75.89%, and an optimum absorption capacity of 29.4%. In future research, it is necessary to vary the concentration of each type of plasticizer and conduct a simple degradation test